Hydrothermal growth of ZnO nanoparticles on the surface of two kinds of Ti3C2 co‐catalysts with different interlayer spacing towards enhanced photocatalytic activity. (2nd August 2022) - Luo, Qiang; Wu, Yan; Chen, Jibing; Cai, Qizhou
Abstract: One of the methods for improving photocatalytic efficiency is using suitable co‐catalysts which can promote the separation of photogenerated electrons and holes. In this study, a typical MXene material, layered Ti3 C2, was selected as a co‐catalyst and acquired by selectively etching Al element from Ti3 AlC2 using hydrogen fluoride (HF), and then the interlayer spacing of Ti3 C2 was reduced through ultrasonic oscillation treatment. By subsequent hydrothermal reactions, the ZnO nanoparticles successfully grew on the surface of two kinds of layered Ti3 C2 without and with ultrasonic oscillation treatment (Ti3 C2 and Ti3 C2 ‐U), thus yielding two ZnO/Ti3 C2 composite photocatalysts (ZTX and ZTUX samples), respectively. Compared with the pure ZnO, ZTX and ZTUX samples have significantly improved photocatalytic activity, which arises from the efficient separation of photogenerated electrons and holes depending on the appropriate Fermi level position of Ti3 C2 . Besides, the ZTUX photocatalysts on the whole exhibit higher photocatalytic activity compared with the ZTX photocatalysts, depending on narrower layer spacing of Ti3 C2 ‐U which facilitates transport of photogenerated electrons.